Germaine de Staël & Benjamin Constant : a dual biography - Winegarten, Renee (Yale University Press, 2008)
When they first met in 1794, shortly after the Reign of Terror, Germaine de Staël and Benjamin Constant were both in their twenties, both married, and both outsiders. She was already celebrated and a published writer, whereas he, though ambitious, was unknown. This compelling dual biography tells the extraordinary story of their union and disunion, set against a European background of momentous events and dramatic social and cultural change. Renee Winegarten offers new perspectives on each of the protagonists, revealing their rare qualities and their all-too-human failings as well as the complex nature of their debt to one another. Their passionate and productive relationship endured on and off for seventeen years. Winegarten traces their story largely through their own words-letters and autobiographical writings-and illuminates the deep intellectual and visceral bond they shared despite disparate personalities and gifts. Exploring their relationships with Napoleon and the Bourbons, their different responses to the momentous upheavals of postrevolutionary France, their support of individual liberty with order, and more, the book concludes with an appreciation of de Staël's and Constant's singular contributions to a new literature and to the history of liberty.